Effects of irrigation regimes and nitrogen management practices on wheat productivity, soil health, and co2 equivalent ghg emissions in rainfed environments (Bangladesh Journal of Botany, 2025)
This study evaluates various properties of soil under different nitrogen management practices and irrigation regimes in wheat. The highest yield (3.71 t/ha) was observed with 100% recommended dose of nitrogen surpassing other nitrogen treatments by 7%. Higher nitrogen doses applied into soil recorded highest microbial biomass carbon (242.97 µg C/g) soil) which was 31.64% more than control, also had the maximum fluorescein diacetate activity (0.38 µg fluorescein/g/soil/h) and highest dehydrogenase activity (5.96 INTF/g/hr soil) leading to a more biologically compatible ecosystem. 50% RDN + two nano-urea sprays resulted in the lowest CO2 equivalent emissions per ton of grain, offering a more sustainable approach. CO2 equivalent emission per ton of grain under lower number of irrigation was 16.42% higher compared to highest number of irrigation. The strong correlation between microbial activity and yield highlights the importance of nitrogen management for enhancing productivity and soil health.Bangladesh J. Bot. 54(2): 277-284, 2025 (June)